The Influence Of Facilities, Social Interaction And Service Quality On Patient Satisfaction At The Kemina Dental Care Clinic - Joseph Putra Aqzha; Sumardin Sumardin; Septa Diana Nabella; Amirullah Amirullah (Cita konsultindo, 2024)
Patients who undergo treatment at a dental clinic will certainly evaluate and assess all aspects that occur because the patient feels firsthand what is provided by the clinic. Patients certainly have the right to give an assessment of what is experienced when treatment at the Kemina Dental Care dental clinic. This study aims to determine the effect on facilities, social interactions and service quality on Kemina Dental Care dental clinic patients. This research was conducted using a survey method with a Google Form questionnaire to patients at the Kemina Dental Care dental clinic and analyzed by multiple linear regression using the SPSS For Windows Version 25.0 application, namely by processing descriptive analysis data, and multiple regression analysis. The number of samples used was 100 patients who received treatment at the clinic. The results showed that facilities, social interaction and service quality have a positive and significant influence on patient satisfaction at the Kemina Dental Care dental clinic. This research is expected to illustrate that patient satisfaction can be used as a direction to continue to prioritize patient needs.